Parameter Estimation of Soil Water Retention and Thermal Conductivity Curves Using HYDRUS‐1D and Inverse Solution - Tehrani, Ashkan; Liaghat, Abdolmajid; Delbaz, Reza (European journal of soil science, 2025)
ABSTRACT Soil water retention curve (SWRC) and thermal conductivity curve (TCC) are crucial soil properties affecting water flow and plant growth in soils. This study investigated simultaneous SWRC and TCC parameter estimation using an inverse solution approach. Water and heat movement in soil were modelled in two soil column experiments, including infiltration with warm water (IWW) and evaporation with heat pulse (EHP), using the HYDRUS‐1D package. For the IWW experiment, two scenarios were considered, each based on a selection of parameters for the inverse solution. For the EHP experiment, 13 scenarios were developed by varying combinations of heat pulses and soil suction sensors as inputs. Unique solutions were obtained in the first IWW, fifth EHP, and 12th EHP scenarios. The first IWW scenario estimated two SWRC parameters (empirical shape parameters, α and n) and three TCC parameters (empirical parameters in soil thermal conductivity function, b1, b2 and b3) using the temperature profile and cumulative infiltration as inputs. The fifth EHP scenario estimated five SWRC parameters (saturated [θs] and residual [θr] water content, saturated hydraulic conductivity Ks, α and n) and three TCC parameters (b1, b2 and b3) using three heat pulses and four tensiometers data as input to the model. The results showed both experiments could estimate SWRC and TCC, with EHP estimating up to eight parameters compared to five for IWW. The 12th EHP scenario (two heat pulses and two tensiometers) provided a unique solution using less input data, offering a more convenient approach, though with slightly wider bounds of estimated parameters.